Molecular Typing and Carbapenem Resistance Mechanisms of Pseudomonas aeruginosa Isolated From a Chinese Burn Center From 2011 to 2016 - Yin, Supeng; Chen, Ping; You, Bo; Zhang, Yulong; Jiang, Bei; Huang, Guangtao; Yang, Zichen; Chen, Yu; Chen, Jing; Yuan, Zhiqiang; Zhao, Yan; Li, Ming; et al. (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa is the leading cause of infection in burn patients. The increasing carbapenem resistance of P. aeruginosa has become a serious challenge to clinicians. The present study investigated the molecular typing and carbapenem resistance mechanisms of 196 P. aeruginosa isolates from the bloodstream and wound surface of patients in our burn center over a period of 6 years. By multilocus sequence typing (MLST), a total of 58 sequence types (STs) were identified. An outbreak of ST111, a type that poses a high international risk, occurred in 2014. The isolates from wound samples of patients without bacteremia were more diverse and more susceptible to antibiotics than strains collected from the bloodstream or the wound surface of patients with bacteremia. Importantly, a large proportion of the patients with multisite infection (46.51%) were simultaneously infected by different STs in the bloodstream and wound surface. Antimicrobial susceptibility testing of these isolates revealed high levels of resistance to carbapenems, with 35.71% susceptibility to imipenem and 32.14% to meropenem. To evaluate mechanisms associated with carbapenem resistance, experiments were conducted to determine the prevalence of carbapenemase genes, detect alterations of the oprD porin gene, and measure expression of the ampC β-lactamase gene and the mexB multidrug efflux gene. The main mechanism associated with carbapenem resistance was mutational inactivation of oprD (88.65%), accompanied by overexpression of ampC (68.09%). In some cases, oprD was inactivated by insertion sequence element IS1411, which has not been found previously in P. aeruginosa. These findings may help control nosocomial P. aeruginosa infections and improve clinical practice.